A case study on the impact of PDRM mobile patrol vehicle visual identity / Mohd Azlizan Jamaludin - Jamaludin, Mohd Azlizan (2015)
This research reports the impact of visual identity towards image building of Polis DiRaja Malaysia (PDRM) by focusing Mobile Patrol Vehicle (MPV) as a case study. The scope of study includes public respondents from Shah Alam, Selangor Darul Ehsan. The objective of this study is threefold. The first objective is to understand the impacts of visual identity effectiveness towards PDRM. The second objective is to investigate the relevant elements towards the characteristics of the visual identity of PDRM. The third objective is to uphold the visual identity of PDRM as the law and enforcement agencies in order to perceive the public community awareness towards the police institution. This has led to the following implications: 1. The identification of general perceptions of public perception, which are most relevant for the visual identity of PDRM; 2. The development of an understanding of how these perceptions, expressed as adjectives, influences or can be used as a basis for selecting a range of factors and characteristics typically used in MPV design, such as form features, form elements, and form principles; and 3. The exploration of applying selected bipolar adjectives as spectra for understanding visual identity of PDRM. The study has shown that there are valid correlations between public perception on brand image and identity, graphic stripe design, and public perception on PDRM. This justifies the search on how these selected public perceptions can be used as a foundation for image building of PDRM as an enforcement body in relation to MPV design.